A poisson autoregressive model to understand COVID-19 contagion dynamics - Arianna Agosto; Paolo Giudici (Risks, 2020)
We present a statistical model which can be employed to understand the contagion dynamics of the COVID-19, which can heavily impact health, economics and finance. The model is a Poisson autoregression of the daily new observed cases, and can reveal whether contagion has a trend, and where is each country on that trend. Model results are exemplified from some observed series.
Keywords: 330; poisson autoregressive models; contagion; predictive monitoring